2010
DOI: 10.1177/0333102410375724
|View full text |Cite
|
Sign up to set email alerts
|

Differences in cervical musculoskeletal impairment between episodic and chronic tension-type headache

Abstract: Active MTrPs in the craniocervical region contribute to triggering or maintenance of TTH and posture or neck mobility may be a result of chronic headache.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
2
23

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 44 publications
3
68
2
23
Order By: Relevance
“…examination tests (Lous and Olesen 1982;Langemark and Olesen 1987;Bovim 1992;Hatch et al 1992;Garrett et al 1993;Jensen et al 1993;Kidd and Nelson 1993;Watson and Trott 1993;Jensen 1996;Lipchik et al 1996;Sand et al 1997;Zwart 1997;Ashina et al 1999;Jull et al 1999Jull et al , 2007Neufeld et al 2000;Dumas et al 2001;Mørk et al 2003;Giacomini et al 2004;Fernández-de-las-Peñas et al 2006;Fernández-de-Las-Peñas et al 2006a, 2006b, 2007Sandrini et al 2006;Zito et al 2006;Amiri et al 2007;Glaros et al 2007Glaros et al , 2007Ogince et al 2007;Hall et al 2008Hall et al , 2010Hall et al , 2010Bevilaqua-Grossi et al 2009;Peddireddy et al 2009;Uthaikhup et al 2009;Sohn et al 2010Sohn et al , 2013Stuginski-Barbosa et al 2010;Melo et al 2012;Watson and Drummond 2012;Marchand et al 2014;Tali et al 2014). …”
Section: A C C E P T E D Accepted Manuscriptunclassified
“…examination tests (Lous and Olesen 1982;Langemark and Olesen 1987;Bovim 1992;Hatch et al 1992;Garrett et al 1993;Jensen et al 1993;Kidd and Nelson 1993;Watson and Trott 1993;Jensen 1996;Lipchik et al 1996;Sand et al 1997;Zwart 1997;Ashina et al 1999;Jull et al 1999Jull et al , 2007Neufeld et al 2000;Dumas et al 2001;Mørk et al 2003;Giacomini et al 2004;Fernández-de-las-Peñas et al 2006;Fernández-de-Las-Peñas et al 2006a, 2006b, 2007Sandrini et al 2006;Zito et al 2006;Amiri et al 2007;Glaros et al 2007Glaros et al , 2007Ogince et al 2007;Hall et al 2008Hall et al , 2010Hall et al , 2010Bevilaqua-Grossi et al 2009;Peddireddy et al 2009;Uthaikhup et al 2009;Sohn et al 2010Sohn et al , 2013Stuginski-Barbosa et al 2010;Melo et al 2012;Watson and Drummond 2012;Marchand et al 2014;Tali et al 2014). …”
Section: A C C E P T E D Accepted Manuscriptunclassified
“…Studies of CTTH patients done in Spain and Korea found an average of 1.9 and 2.4 active MTrPs per CTTH patient respectively, when examining three to four head and neck muscles bilaterally. 13,16 In a subsequent study led by the same Spanish researcher, a mean number of seven active MTrPs per CTTH patient were found when examining six head and neck muscles bilaterally. 21 In the current study, which examined five head and neck muscles bilaterally, a mean number of 4.9 active MTrPs per CTTH patient was found.…”
Section: Conflict Of Interest -No Conflict Of Interest To Declarementioning
confidence: 98%
“…The suboccipital muscles also exhibited the highest number of active MTrPs in one of the Spanish studies, 21 unlike the Korean study, where the upper trapezius was more often involved (60.9% of patients) as compared with the suboccipital (26.1%) and temporalis (8.7%) muscles. 16 Simons et al have noted that the trapezius is probably the muscle that is most often affected by MTrPs. 5 The relatively low prevalence of active MTrPs in the trapezius in our study may relate to differences in daily activities in our study population, compared with other study populations.…”
Section: Conflict Of Interest -No Conflict Of Interest To Declarementioning
confidence: 99%
See 2 more Smart Citations